2016
DOI: 10.1016/j.jenvman.2016.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Landfill leachate treatment by sequential membrane bioreactor and electro-oxidation processes

Abstract: Combination of high performance membrane bioreactor (MBR) equipped with ultrafiltration and electro-oxidation process (EOP) by boron-doped diamond electrode (BDD) was used to effectively treat highly contaminated old landfill leachate. MBR and EOP were optimized for raw and pretreated landfill leachate. Seasonal changes dramatically affected the both processes' performance, as the landfill leachate was ¾ more concentrated in winter. For MBR, organic load rate of 1.2 gCOD/L/day and sludge retention time of 80 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(27 citation statements)
references
References 20 publications
0
27
0
Order By: Relevance
“…Zolfaghari et al [173] suggested the combination of a membrane bioreactor (MBR) equipped by ultra-filtration (UF) and an electro-oxidation process (EO) with a boron-doped diamond electrode (BDD) in order to effectively treat highly contaminated, medium-old landfill leachate (BOD/COD = 0.14-0.3). The membrane bioreactor used in this study is a submerged hollow-fiber UF with a nominal pore size of 0.04 µm and a total filtration surface area of 0.047 m 2 .…”
Section: Mbr-uf-eo (Québec Canada)mentioning
confidence: 99%
See 1 more Smart Citation
“…Zolfaghari et al [173] suggested the combination of a membrane bioreactor (MBR) equipped by ultra-filtration (UF) and an electro-oxidation process (EO) with a boron-doped diamond electrode (BDD) in order to effectively treat highly contaminated, medium-old landfill leachate (BOD/COD = 0.14-0.3). The membrane bioreactor used in this study is a submerged hollow-fiber UF with a nominal pore size of 0.04 µm and a total filtration surface area of 0.047 m 2 .…”
Section: Mbr-uf-eo (Québec Canada)mentioning
confidence: 99%
“…The utilization of a radical scavenger after electro-oxidation or keeping electro-oxidized landfill leachate in a storage tank before introduction into the aeration basin could be a solution to this challenge [173].…”
Section: Mbr-uf-eo (Québec Canada)mentioning
confidence: 99%
“…The membrane bioreactor is widely used in landfill leachate treatment due to its high performance in the removal of ammonia. The effluent of this system contains compounds resisting to biodegradation (such as humic substances, and a little amount of ammonia and heavy metals) for which advanced oxidation processes (AOPs) are amongst suitable treatment methods [20]. The Advantages of this method are less sludge production, effluent of high quality, high concentration of nitrifying bacteria, and effective performance of nitrification could be mentioned [1].…”
Section: Aerobic Biological Treatmentmentioning
confidence: 99%
“…Partial of 80% removal of nitrogen in aerated Lagoon was done by ammonia evapora- Moving-bed biofilm reactor (MBBR) 800 -2000 20 [24] 7500 -7900 8 [25] Membrane bioreactor (MBR) 1000 -3000 80 -83 [26] 1550 63 [20] 14,000 80 [27] aerobic sequencing batch reactor (ASBR) 4000 87 [21] 3200 30 [28] Aerated lagoons 1740 75 [22] 5518 97 [29] tion [22]. In another study, the use of this method in leachate treatment led to the removal of 97% COD and 92% ammonia nitrogen [29].…”
Section: Aerated Lagoon Process Performancementioning
confidence: 99%
“…Due to the complexation of metals with each other and organic carbon, 24 to 100% of heavy metals are presented in colloidal phase (the size below 10 nm) (Jensen et al, 1999). It is worth mentioning that precipitation of metal by phosphorus inside landfills dramatically decreases their concentration in the leachate (Zolfaghari et al, 2016b). …”
mentioning
confidence: 99%